ANALISIS KONTEN LITERASI KESEHATAN DR GIA PRATAMA DI MEDIA SOSIAL INSTAGRAM PADA AKUN @GIAPRATAMAMD - Raihan Al Hakiim, Valerieanda; Mustika Chairil, Augustin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the forms of health literacy applied by dr. Gla Pratama in his Instagram content on the @giapratamamd account as a digital health education medium. This research employs a qualitative approach with qualitative content analysis method, analyzing 16 Instagram posts uploaded during February 2026. The analysis framework is based on Don Nutbeam's three-level health literacy theory, namely functional health literacy, interactive health literacy, and critical health literacy. The results reveal that all analyzed content contains elements of health literacy, with functional health literacy as the most dominant form, present in nearly all content. It is manifested through simplification of complex medical terms using everyday analogies and metaphors, as well as storytelling approaches that bridge medical knowledge with audience experience. Interactive health literacy appears as complementary dimension, encouraging audiences to actively use health information in daily life through direct calls to action and participatory approaches. Critical health literacy, while least frequent, is the most strategically significant, found explicitly in content debunking misconceptions about dengue fever and gastric acid. Overall, dr. Gla Pratama'S Instagram account has successfully functioned as a digital health education medium that Incorporates all three levels of health iteracy according to Nutbeams framework, contributing to public health literacy improvement in the digital era.